PENGARUH TERPAAN DAN KUALITAS INFORMASI PADA AKUN INSTAGRAM @ANIMOLIFE TERHADAP PEMENUHAN KEBUTUHAN INFORMASI FOLLOWERS - Muhamad Duky Nurhaditio; Eko Hartanto (Asosiasi Dosen Muda Indonesia, 2023)
@animolife is an account that creates content about self-development. This study aims to find out this study aims to find out how the influence of social media exposure of Instagram accounts @animolife and the quality of instagram social information @animolife on meeting the information needs of followers. In this study using the theory of Uses and effects, this theory is a theory that explains the relationship between mass communication conveyed through mass media, which causes an effect for users of the mass media. This research was conducted quantitatively with a descriptive approach and used questionnaires as data collection instruments. The sampling technique is determined by the slovin formula. The population of this study was @animolife followers which amounted to 108,000 followers with a total sample of 400 respondents. In this study, it used a sample technique, namely puposive sampling. The results showed that there was an influence on the exposure and quality of social media information on Instagram accounts @animolife on meeting the information needs of followers by 59.4%.